Synthesis of 3‐D Coronal‐Solar Wind Energetic Particle Acceleration Modules. Issue 6 (24th June 2014) - Schwadron, Nathan A.; Gorby, Matt; Török, Tibor; Downs, Cooper; Linker, Jon; Lionello, Roberto; Mikić, Zoran; Riley, Pete; Giacalone, Joe; Chandran, Ben; Germaschewski, Kai; Isenberg, Phil A.; et al.
Key Points Radiation from low corona Prompt SEP events from CME Large doses in 2 h